NUGGET SUSBTITUSI IKAN KEMBUNG DAN TEPUNG TEMPE SEBAGAI PMT TINGGI PROTEIN BALITA USIA 12 – 59 BULAN: Nugget Substitution Mackerel Fish and Tempeh Flour as High Protein Pmt for Toodler 12 – 59 Months - Permatasari, Oktavina (Media Gizi Pangan, 2024)
Compementary Food (PMT) is food given to toddlers to meet the nutritional requirements that toddlers get from the daily food. Toddler Additional Food is nutrition supplementation in the form of additional food such as nuggets, meatballs, sausages, etc. for toddlers 6 – 59 months in the underweight category. In this research, used local food and functional foods are mackerel fish and tempeh flour to raw materials in complementary food of nuggets for toddlers of obtaining high protein content and other nutrients. This research is a quantitative with experimental methods using a completely randomized design with one factor, namely the formulation of tempeh flour nuggets with the addition of mackerel with three formulations. The object studied was the nugget treatment carried out in this research, the differences in the composition of the raw materials and the nugget characteristics. Formulation of three nugget for organoleptic quality test with 40 panelists mothers of toddlers. From the results of the organoleptic quality test, can be concluded that formulation 02 nuggets have the highest value can interpreted as being acceptable compared to formulation 01 or 03 nuggets from the aspects of taste, color, smell, and texture. The nugget formulation most preferred by the panelists explained that the protein content was 11.96%, which was higher than the control nugget (without the addition of tempeh flour and mackerel fish) on 4.85%. For toddlers aged 1 - 5 years who consume two nuggets equivalent to 60 grams every day can meet the daily protein of 35.9% - 28.7% of the protein requirement based on the 2019 Recommended Dietary Allowances (RDA).